1994
DOI: 10.1177/0022022194253004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring, Locus of Control, and Social Encounters of Chinese and New Zealand Students

Abstract: Characteristics of daily encounters were studied as a function of self-monitoring and locus of control in Chinese and European students. Complementary predictions based on both the individualistic versus collectivistic cultural distinction and self-monitoring theory were supported by the results. The Chinese sample showed higher self-monitoring scores, were more external in their locus of control, made fewer daily contacts that were more task oriented, and involved higher levels of self-disclosure than New Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 25 publications
4
42
0
4
Order By: Relevance
“…For example, it has been suggested that cultures that emphasize autonomy and freedom promote values in individuals that are congruent with an internal locus of control orientation (Hamid 1994;McLaughlin and Saccuzzo 1997;Morris and Peng 1994). Minority groups in the US, in contrast, have been found in some studies to hold a more external locus of control, which is consistent with their collectivistic views (McCabe et al 2008;Norenzayan, and Lee 2010;Threlfall et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…For example, it has been suggested that cultures that emphasize autonomy and freedom promote values in individuals that are congruent with an internal locus of control orientation (Hamid 1994;McLaughlin and Saccuzzo 1997;Morris and Peng 1994). Minority groups in the US, in contrast, have been found in some studies to hold a more external locus of control, which is consistent with their collectivistic views (McCabe et al 2008;Norenzayan, and Lee 2010;Threlfall et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Also, the connection between internality/externality has been related to national culture (Hamid, 1984;Hui, 1982), often relating locus externality to the Individualism/Collectivism dimension of Hofstede's well-known Theory of Culture (1979,1980). The consistent trend within this research suggests clearly that individuals from collectivistic societies (such as Taiwan) are more externally oriented.…”
Section: Hypothesesmentioning
confidence: 99%
“…Furthermore, studies have shown that collectivist Asians (e.g., Chinese and Japanese) are more external in their general locus of control (LOC) than individualistic Americans and other western nations (Hamid, 1994;Hui, 1982). Nations in eastern Europe that were formally under control of the Soviet Union are also collectivistic.…”
Section: Work Locus Of Control and Individualism±collectivismmentioning
confidence: 99%